Study on impacts of farmer-led research supported by civil society organizations - Wettasinha, C; Waters-Bayer, Ann; Veldhuizen, L. van; Quiroga, G; Swaans, Cornelis P.M. (CGIAR Research Program on Aquatic Agricultural Systems, 2014)
The CGIAR Research Program on Aquatic Agricultural Systems (AAS) program, together with the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), asked Prolinnova — an NGO-led multistakeholder international network that promotes local innovation processes in agriculture and natural resource management — to help them explore the approaches, outcomes and impacts of informal research and development facilitated by CSOs. Basing their research on 11 case studies from Africa, Asia and Latin America, which were drawn from over 100 cases that were identified and vetted, the study team assessed the extent to which farmer-led processes of research and innovation in agriculture and natural resource management led to improvements in rural livelihoods. This report describes farmer-led research findings and their dissemination, and analyzes available evidence on the impact of farmer-led approaches to agricultural research and development on rural livelihoods, local capacity to innovate and adapt, and influence on governmental institutions of agricultural research and development. It then draws lessons for pursuing this type of approach and for future partnerships between actors in both formal and informal agricultural research and development who seek common goals in serving smallholder communities.